Automatic Segmentation of Multiple Organs on 3D CT Images by Using Deep Learning Approaches - Zhou, Xiangrong (Advances in experimental medicine and biology, 2020)
This chapter focuses on modern deep learning techniques that are proposed for automatically recognizing and segmenting multiple organ regions on three-dimensional (3D) computed tomography (CT) images. CT images are widely used to visualize 3D anatomical structures composed of multiple organ regions inside the human body in clinical medicine. Automatic recognition and segmentation of multiple organs on CT images is a fundamental processing step of computer-aided diagnosis, surgery, and radiation therapy systems, which aim to achieve precision and personalized medicines. In this chapter, we introduce our recent works on addressing the issue of multiple organ segmentation on 3D CT images by using deep learning, a completely novel approach, instead of conventional segmentation methods originated from traditional digital image processing techniques. We evaluated and compared the segmentation performances of two different deep learning approaches based on 2D- and 3D deep convolutional neural networks (CNNs) without and with a pre-processing step. A conventional method based on a probabilistic atlas algorithm, which presented the best performance within the conventional approaches, was also adopted as a baseline for performance comparison. A dataset containing 240 CT scans of different portions of human bodies was used for training the CNNs and validating the segmentation performance of the learning results. A maximum number of 17 types of organ regions in each CT scan were segmented automatically and validated with the human annotations by using ratio of intersection over union (IoU) as the criterion. Our experimental results showed that the IoUs of the segmentation results had a mean value of 79% and 67% by averaging 17 types of organs that were segmented by the proposed 3D and 2D deep CNNs, respectively. All results using the deep learning approaches showed better accuracy and robustness than the conventional segmentation method that used the probabilistic atlas algorithm. The effectiveness and usefulness of deep learning approaches were demonstrated for multiple organ segmentation on 3D CT images.